Early CD8 T-cell memory precursors and terminal effectors exhibit equipotent in vivo degranulation - Yuzefpolskiy, Yevgeniy (Cell Mol Immunol, 2015)
Early after priming, effector CD8 T cells are distinguished into memory precursor and short-lived effector cell subsets (MPECs and SLECs). Here, we delineated a distinct in vivo heterogeneity in killer cell lectin-like receptor G1 (KLRG-1) expression, which was strongly associated with diverse MPEC and SLEC fates. These in vivo MPECs and SLECs expressed equivalent levels of cytotoxic molecules and effector cytokines. Using a unique in vivo degranulation assay, we found that the MPECs and SLECs similarly encountered infected target cells and elaborated equivalent levels of cytotoxicity in vivo. These data provide direct in vivo evidence that memory-fated cells pass through a robust effector phase. Additionally, the preferential localization of the MPECs in the lymph nodes, where a lesser degree of cytotoxicity was elaborated, suggests that the MPECs may be protected from excessive stimulation and terminal differentiation by virtue of their differential tissue localization. These data provide novel mechanistic insights into the linear decreasing potential model of memory differentiation.